Impact evaluation and client satisfaction of Northwest Microfinance Expansion Project - Barua, Proloy; Munshi Sulaiman (BRAC Research and Evaluation Division (RED), 2020)
Bangladesh is known for its microfinance outreach. However. the density of microfinance is not evenly distributed. The poorer region, specially the northwestern part of Bangladesh has long been underserved by the microfinance institutions (MFI). BRAC"s Northwest Microfinance Expansion (NWME) project was initiated in 2002 to increase outreach in that region. Though the impact of microfinance is well established among the practitioners. this study was initiated to investigate whether BRACs microfinance expansion in that region had any effect on the well-being of the beneficiaries. We found some concrete evidences of impact in different domains especially in their asset holding. Apart from impact evaluation, the study also looked at the level of satisfaction among microfinance participants. The determinants of client dropout have been explored to see whether and how much effect does satisfaction has on exit decision. Poverty of the participants, variation in economic status within the groups, availability of alternative service providers, level of client loyalty along with the overall satisfaction of the clients with the services were found to have significant influence on dropout.